Pengaruh Online Promotion Dan Persepsi Kemudahan Terhadap Keputusan Penggunaan E-Wallet Ovo Pada Masyarakat - Azzahra Desire Safira Siahaan; Muthya Rahmi Darmansyah; Hesti Sabrina; Irwansyah Putra (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
E-wallet users as digital wallets are the choice of the people of Medan City, especially the OVO e-wallet for online system payments in transactions. It is suspected that the increase in the use of the OVO e-wallet is due to online promotion factors and perceived ease of use. The purpose of the study was to determine the effect of online promotion and perceived ease of use on the decision to use the OVO e-wallet in the community. The research method is quantitative and associative. The population is the people of Medan Sunggal District, Medan City, totaling 140,138 people and the number of samples is 100 people. The research data comes from primary data and the data collection process uses a questionnaire. The analysis technique using statistical models consists of validity, reliability, classical assumptions, multiple linear regression, t-test, F-test and coefficient of determination (R2) using SPSS (Statistical Product and Service Solutions) software version 25. The results of the study that partially there is an influence of online promotion and perceived ease of use on the decision to use the OVO e-wallet with each t-count value (7.578 and 2.110) greater than t-table (1.660) and a significance level (0.000 and 0.037) less than 0.05. From the F test, it was obtained that Fcount> Ftable (64.079> 3.090) with a significance level (0.000 <0.05), so the hypothesis is accepted, simultaneously online promotion and perceived ease of use have a positive and significant effect on the decision to use the OVO e-wallet. The R Square value is 0.569 which means that 56.9% of the variation of independent variables (online promotion and perceived ease) can explain the decision to use the OVO e-wallet and the remaining 431% is influenced by other variables.